Text Analysis of PPKM Rules Legal Documents - Sri Rahayuni, Ni Ketut (e-Journal of Linguistics, 2025)
This study aims to analyze the differences in linguistic elements that appear in the government rules relating to PPKM (lockdown) issued by the central government and provincial government referring to the same thing and also to analyze the multiple interpretations that appear in the two regulations. Forensic linguistics is the basis of the study in this research on the text of the PPKM rules. The data analyzed in this study is the text of regulations regarding PPKM published between the central government and provincial government using a qualitative descriptive method (Bungin, 2015), and applying content analysis techniques. The results of this study indicate that there are a number of contradictory or different applications of the rules referring to the same point or item between the main rules of the central government and the derivative rules by the provincial government regarding PPKM activities. With those differences in the two rules, this could make the community or people as the object or target of the rules get confused and have the potential to violate the rules themselves. Based on these results, it is necessary to synchronize or match the main rules from the central government and the rules from provincial governments as derivative rules so that people will not get confused and have the potential to break the rules. In addition, ambiguity of meaning can also be avoided.